The role of education in promoting positive attitudes towards migration at times of stress - Borgonovi, Francesca (OECD Education Working Papers, 2018)
The paper examines the role of education in shaping individuals' attitudes towards migration in European countries using data from the 2012, 2014 and 2016 editions of the European Social Survey (rounds 6, 7 and 8). Results indicate that, despite the large influx of migrants experienced by many European countries in 2015, attitudes towards migration reported by 25-65 year olds did not vary significantly over the period considered. Education was strongly associated with individuals' attitudes towards migration although the strength of the association and how the association changed over time varied greatly across countries. On average a difference of one standard deviation in educational participation is associated with a difference of 20% of a standard deviation in reported opposition to migration. Around three quarters of the association between education and opposition to migration can be explained by the lower economic threat, cultural threat and prejudice that individuals with higher educational participation experience